Evaluating the methodology of the studies that dealt with the Palestinian-Israeli negotiations - Maala, Abdel Salam; bin Yatiban, Amin Rashid (Journal of Humanities & Social Sciences, 2017)
The Palestinian-Israeli negotiating experience has attained the researchers' attention, because of the specificity of the conflict first, and because of the long period of time it has consumed without reaching an acceptable solution to both parties. There is a fair amount of studies, which have dealt with the negotiating experience mentioned, and through which it has tried to explore the reasons that pushed the process into deadlock, in an attempt to reach a correct perception helps to analyze the Palestinian-Israeli negotiation experience. This study aims at evaluating the previous studies, which have dealt with the Palestinian-Israeli negotiating process, through focusing on the methodology those studies used to assess and analyze the negotiating experience, using a hypothesis considers that the analytical method adopted by those studies suffers a clear deficiency. The study draws its methodology through highlighting the factors addressed in previous studies, and was considered a reason for the negotiation process to reach to a deadlock, and again highlighting other factors that critically affect the outcomes of the negotiating process, but have been neglected by Previous studies. In light of this, the study attempts to explore whether the methodology adopted by previous studies to assess and analyze the Palestinian-Israeli negotiating experience was adequate or not.
Keywords: Palestinian-Israeli negotiations; methodological evaluation; previous studies; negotiation intractability